2003
DOI: 10.1002/art.10906
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of locomotor ability two months after total knee arthroplasty for severe osteoarthritis

Abstract: Objective. To identify preoperative predictors of locomotor ability 2 months after total knee arthroplasty (TKA). Methods. Sixty-five participants scheduled for a first TKA were recruited. The dependent variable was the distance covered during the 6-minute gait test 2 months after TKA. The independent variables, measured before surgery, were grouped into 3 categories: 1) personal; 2) organic system, and 3) capability variables. Multiple regression analyses were conducted to determine the best predictors of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 136 publications
5
32
0
2
Order By: Relevance
“…Comorbidity is defined as a diagnosis or a medical condition related to health (22). The current study observed that 76% of the patients presented one or more comorbidities (22.4% one comorbidity, 53.6% two or more), which was in line with the average comorbidity in the Spanish Health System.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Comorbidity is defined as a diagnosis or a medical condition related to health (22). The current study observed that 76% of the patients presented one or more comorbidities (22.4% one comorbidity, 53.6% two or more), which was in line with the average comorbidity in the Spanish Health System.…”
Section: Discussionsupporting
confidence: 79%
“…Bachmeier maintained that previous use of joint prostheses did not lead to a worse result after the surgery, as in the current study (17). Parent (22) and Katz (26) reported that preoperative factors were the predictors for mobility and associated outcomes.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The preoperative 6MWT also predicted gait endurance in the first month after TKA. This finding is supported by Parent and Moffet 37) , who showed that the preoperative 6MWT, knee pain, and knee flexion predict locomotor ability 2 months after TKA with good accuracy. This association probably reflects the fact that the baseline value of a given measure is often a strong predictor of the same measure later in time 38,39) .…”
Section: Discussionsupporting
confidence: 60%
“…4,5 Lograr una función adecuada depende de varios factores, tales como el rango de movilidad, la fuerza muscular, la estabilidad articular, el dolor y las expectativas del paciente. [6][7][8] El rango de movilidad posoperatorio es un aspecto importante en el resultado final. Ciertos pacientes hoy en día solicitan mayor rango de movimiento, porque sus estilos de vida son más activos, son más jóvenes o por requerimientos socioculturales.…”
Section: Introductionunclassified